Snacks, beverages, and physical activity during volunteer-led out-of-school-time programs: a cross-sectional analysis. - Economos, Christina D.; Anzman-Frasca, Stephanie.; Koomas, Alyssa H.; Chan, Grace.; Folta, Sara C.; Heck, Julianne.; Newman, Molly.; Sacheck, Jennifer M. (2017)
Background: Tens of millions of children regularly participate in out-of-school-time (OST) programs, providing an opportunity for child health promotion. Most research on OST has focused on structured, staff-led after-school programs, as opposed to volunteer-led programs such as enrichment programs and youth sports. The aim of this study was to describe snacks, beverages, and physical activity (PA) practices in volunteer-led OST programs across five organizations in three states.; Keywords: Out-of-school time, After-school programs, Enrichment, Youth sports, Children, Snacks, Beverages, Nutrition, Physical activity.; Springer Open.